2021
DOI: 10.5005/jp-journals-10071-23882
|View full text |Cite
|
Sign up to set email alerts
|

Severe Acute Respiratory Infection Surveillance during the Initial Phase of the COVID-19 Outbreak in North India: A Comparison of COVID-19 to Other SARI Causes

Abstract: A bstract Introduction World Health Organization proposes severe acute respiratory infection (SARI) case definition for coronavirus disease 2019 (COVID-19) surveillance; however, early differentiation between SARI etiologies remains challenging. We aimed to investigate the spectrum and outcome of SARI and compare COVID-19 to non-COVID-19 causes. Patients and methods A prospective cohort study was conducted between March 15, 2020, to August 15,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…53 Interestingly, the only moderately-large prospective study in which data for COVID and non-COVID cases were collected at the same location over the exact same time period, and in which multivariable analysis was performed to identify predictors of mortality found the APACHE-II score to be only significant predictor, with mechanical ventilation predictive in non-COVID cases. 40 Note that we found both to be predictive of both COVID and non-COVID related ARDS. One potential explanation for this difference is that our study had 160 and 530 COVID and non-COVID cases, respectively, vs. just 95 and 117 in the Indian study.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…53 Interestingly, the only moderately-large prospective study in which data for COVID and non-COVID cases were collected at the same location over the exact same time period, and in which multivariable analysis was performed to identify predictors of mortality found the APACHE-II score to be only significant predictor, with mechanical ventilation predictive in non-COVID cases. 40 Note that we found both to be predictive of both COVID and non-COVID related ARDS. One potential explanation for this difference is that our study had 160 and 530 COVID and non-COVID cases, respectively, vs. just 95 and 117 in the Indian study.…”
Section: Discussionmentioning
confidence: 62%
“…One exception that appears to have overcome all the above-mentioned shortcomings was a study conducted in India which compared 95 COVID and 117 non-COVID ARDS patients all treated at a single, tertiarycare, academic hospital from March 15 through August 15, 2020the first wave of COVID-19 in that area. 40 In this study, logistic regression identified higher APACHE-II scores as predictive of mortality in COVID but not non-COVID patients. However, that there were only 212 patients total might have resulted in inadequate statistical power to detect other predictors either distinct to COVID or shared by both COVID and non-COVID ARDS patients.…”
Section: Introductionmentioning
confidence: 58%
“…scrub typhus, malaria); thus the diagnosis of pyomyositis may be overlooked. [18][19][20] Moreover, muscle pain may be absent in up to 25% of cases of pyomyositis. 9 S. aureus remained the most common organism but with a higher proportion (c.50%) of MRSA strains from Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…scrub typhus, malaria); thus the diagnosis of pyomyositis may be overlooked. 1820 Moreover, muscle pain may be absent in up to 25% of cases of pyomyositis. 9…”
Section: Discussionmentioning
confidence: 99%
“…A study from India reported 12 days duration of COVID-19 for hospitalized patients 34 . Another study from Germany also reported an overall hospitalization of 12 (7–20) days for COVID-19 patients needing oxygen supplementation outside the ICU 35 .…”
Section: Methodsmentioning
confidence: 99%